Basic training principles for pre-pubertal swimmers - Rushall, B. S.
ABSTRACT Some principles for the physiological, biomechanical, and psychological development of children in competitive swimming are discussed. It is contended that many performance factors are peculiar for this developmental age-group. They should not be confused with adult training principles or practices. Specialist swimming coaches steeped in specific knowledges for this age-group are essential for designing and implementing programs that stimulate appropriate physical and social development. Main principles: Swimming technique instruction for children should focus on general factors of body alignment/posture, appropriate anatomical positions for direct force production, resistance reduction, and variety in skill experiences and elements. Children are primarily aerobic and respond to exercise stress in a non-differentiated manner.